Impact of Psychotherapy in Psychosis: A Retrospective Case Control Study - Haram, Annbjørg; Fosse, Roar; Jonsbu, Egil; Hole, Torstein (Frontiers in Psychiatry, 2019)
Background: The need for psychological therapies for psychosis has become apparent since long-term antipsychotic drug treatment has a range of adverse side effects, with moderate therapeutic effects at best. Aims: To investigate whether the psychotherapeutic approach, dialogue therapy (DT) has effects beyond standard psychiatric treatment (ST) in both schizophrenia and other psychosis. Methods: A retrospective case-control design, comparing 54 patients with different psychoses who received DT with 54 patients in a control group receiving ST. The groups were matched on diagnosis, age, sex, and treatment start. Outcome measures were Global assessment of functioning (GAF) scores, medications at follows up, and hospital stays after completed outpatient treatment. Results: Mean time in treatment from inclusion to follow-up was 3 years and 5 months. At follow-up, GAF functioning (GAF-F) and GAF symptom (GAF-S) scores both were significantly higher in the DT group than the ST group. Effect sizes (Cohen’s d) were large; 1.8 for GAF-S and 2.1 for GAF-F. At follow-up, the use of psychoactive drugs was significantly reduced despite a shorter time in psychotherapy in the DT group compared to the ST group. Days of hospitalizations after end of treatment in the study period were significantly reduced in both groups compared to the period before start of treatment. Conclusions: The study provides preliminary evidence that dialogue therapy may lead to improvements in symptoms and functioning compared to standard treatment in psychosis.